2021
DOI: 10.1111/jan.14790
|View full text |Cite
|
Sign up to set email alerts
|

“The light at the end of the tunnel”. Discharge experience of older patients with chronic diseases: A multi‐centre qualitative study

Abstract: Aim To explore the experiences of being discharged from hospital of older patients with chronic diseases at time of discharge. Design Multi‐centre descriptive qualitative study. Methods Semi‐structured interviews were conducted with older patients with chronic diseases discharged from two Italian university hospitals, between March 2017 and October 2019. The interviews were audio‐recorded, transcribed verbatim and analysed using inductive content analysis. Several strategies were used to ensure the credibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Our study also shows that older persons have limited opportunities to really influence care design: the scope for action is too small and they experience that they are not given any choices during the video conference itself. Facchinetti et al ( 2021 ) believe that this is because the care staff need to inform, involve and prepare the older persons for the discharge, so that they can handle their condition at home without feeling abandoned. Sinclair et al ( 2020 ) found that functioning coordinated planning of care interventions before discharge has become more important in connection with the outbreak of the Covid‐19 pandemic in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also shows that older persons have limited opportunities to really influence care design: the scope for action is too small and they experience that they are not given any choices during the video conference itself. Facchinetti et al ( 2021 ) believe that this is because the care staff need to inform, involve and prepare the older persons for the discharge, so that they can handle their condition at home without feeling abandoned. Sinclair et al ( 2020 ) found that functioning coordinated planning of care interventions before discharge has become more important in connection with the outbreak of the Covid‐19 pandemic in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…They experience insecurity and feel neglected in a situation unknown to them. Our study also shows that older persons have limited opportunities to really influence care design: the scope for action is too small and they experience that they are not given any choices during the video conference itself Facchinetti et al (2021). believe that this is because the care staff need to inform, involve and prepare the older persons for the discharge, so that they can handle their condition at home without feeling abandoned Sinclair et al (2020).…”
mentioning
confidence: 87%